Overexpression of CD59 inhibits apoptosis of T-acute lymphoblastic leukemia via AKT/Notch1 signaling pathway - Jia, Yanfei (Cancer Cell Int, 2019)
BACKGROUND: T-acute lymphoblastic leukemia (T-ALL) was a hematological malignancy characterized by the accumulation of immature T cells in bone marrow and peripheral blood. In this study, we tried to explore the physiological role of CD59 in T-ALL. METHODS: In this study, we collected the bone marrow samples from 17 T-ALL patients and 38 healthy participants to find differences in CD59 expression patterns. Then, CD59 was over-expressed in T-ALL cell line Jurkat, and its biological functions were detected. In addition, in order to understand the active site of CD59, the Trp40 was mutated. Further, we constructed a mouse model by transplanting Jurkat cells into the nude mice to verify the function of CD59 in vitro. At last, mechanism studies were performed by western blot. RESULTS: We found that the proportion of T lymphocytes expressing CD59 in bone marrow of T-ALL patients was significantly higher than that of healthy individuals. Then, we found that the overexpression of CD59 in Jurkat cells was beneficial to the cell survival by inhibiting apoptosis and promoting IL-2 secretion. In this process, Trp40 of CD59 was a key functional site. Further, the high expression of CD59 inhibited apoptosis of bone marrow and peripheral blood cells, and promoted IL-2 secretion in mouse model. At last, mechanism studies showed that the activation of AKT, STAT5 and Notch1 signaling pathways in Jurkat cells, may be involved in the regulation of apoptosis by CD59; and mutation in the Trp40 affect the interaction of CD59 with these signaling pathways. CONCLUSIONS: In conclusion, CD59 inhibited apoptosis of T-ALL by regulating AKT/Notch1 signaling pathway, providing a new perspective for the treatment of T-ALL. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12935-018-0714-9) contains supplementary material, which is available to authorized users.